2022
DOI: 10.1021/jacsau.1c00410
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Hybrid Electrolytes with Viscosity Controlled Using Ionic Stimulus for Electrochemical Energy Conversion and Storage

Abstract: As renewable energy is rapidly integrated into the grid, the challenge has become storing intermittent renewable electricity. Technologies including flow batteries and CO 2 conversion to dense energy carriers are promising storage options for renewable electricity. To achieve this technological advancement, the development of next generation electrolyte materials that can increase the energy density of flow batteries and combine CO 2 capture and conversion is desired. Liquidlike nanoparticle organic hybrid mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 70 publications
1
28
0
Order By: Relevance
“…Our earlier studies have shown that the polymers in NOHM‐based fluids often exist in multiple states such as tethered, interacting, and free HPE chains. [ 34,35,51 ] Those earlier studies were only focused on NOHM‐I‐HPE, and we anticipated that NOHM‐C‐HPE would lead to different binding interactions in the solution phase, with and without salts. Thus, small‐angle neutron scattering (SANS) experiments were completed to identify the effect of the bond type on the structure and organization of the polymer and nanoparticles in NOHM‐based fluids and electrolytes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our earlier studies have shown that the polymers in NOHM‐based fluids often exist in multiple states such as tethered, interacting, and free HPE chains. [ 34,35,51 ] Those earlier studies were only focused on NOHM‐I‐HPE, and we anticipated that NOHM‐C‐HPE would lead to different binding interactions in the solution phase, with and without salts. Thus, small‐angle neutron scattering (SANS) experiments were completed to identify the effect of the bond type on the structure and organization of the polymer and nanoparticles in NOHM‐based fluids and electrolytes.…”
Section: Resultsmentioning
confidence: 99%
“…This concentration of salt was selected because this was recently found to be near the experimentally observed transition from the ionic stimuli‐responsive regime to the saturation regime of a higher grafting density liquid‐like NOHM‐I‐HPE. [ 51 ] The specific viscosity is a dimensionless measure of the viscosity and was used in this case to directly compare the effect of polymer, nanoparticle, or NOHMs addition to the overall solution viscosity. The specific viscosity (η sp ) can be determined by ηspbadbreak=ηηsηnormals\[ \begin{array}{*{20}{c}}{{\eta _{{\rm{sp}}}} = \frac{{\eta - {\eta _{\rm{s}}}}}{{{\eta _{\rm{s}}}}}}\end{array} \] where η is the viscosity of the solution/electrolyte containing polymer, nanoparticles, or NOHMs and η s is the viscosity of the solvent (e.g., water or 0.1 m KHCO 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations